The Prevalence of Philippine Prescribing, Dispensing, and Use Behavior in Relation to Generic Drugs and their Risk Factors - John Q. Wong; J. Richelcyn M. Baclay; Richelle G. Duque; Patricia Margarita S. Roque; Grace Kathleen T. Serrano; Jenina Olivia A. Tumlos; Aisha-Aziza A. Ronsing (Philippine Institute for Development Studies (PIDS), 2014)
This study was designed to address the issue of compliance of physicians and drugstores to the provisions of Generics Act of 1988. Furthermore, it aims to explore the awareness of consumers on generic medicines to explain current trends and practices in drug prescribing, dispensing, and use. The study utilized a cross-sectional design. It is a descriptive study that assessed four variables: generic drug prescription, generic drug substitution/dispensing, price menu cards, and use of generic drugs. The country was divided into six zones, namely: North Luzon, South Luzon, NCR, Visayas, Mindanao, and ARMM. Stratified cluster random sampling was used to identify which provinces and cities would be included in the study.Data collection techniques used include the following: a survey of consumers coming out of a drugstore (a total of 1,160 respondents), key informant interview of 30 physicians, and focus group discussion with 6 to 11 patients/watchers per zone.The survey revealed that five out of six drugs were written with generic names, with doctors in the public sector prescribing generics significantly more often than those in the private sector. Factors that positively affect generics prescribing behavior are patient's welfare, compliance, patient's financial situation, and fear of punishment. Quality concerns, lack of regulation by FDA, poor recall, patient's preference, and personal experience are factors that negatively affect generics prescribing behavior. Less than half of the consumers were offered with generic alternatives, and even less number of consumers actually asked for the alternative. There is preference for branded medicines over generics. The consumers more likely to purchase generic medicines consulted a public facility, knew the requirement to write generic name, and was influenced by friends and relatives. Because there is already high compliance from drug prescribers, government efforts should now focus on the drugstores and consumers. Drugstore compliance should be regularly monitored, and consumers empowered on their right to know alternatives. Bioequivalence tests should be done to finally put an end to concerns on the quality of generic medicines.
Keywords: 330; Philippines; generics; prescribing; dispensing; drug use; social marketing; cross-sectional survey